(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Social-emotional learning (SEL) is now an integral part of early childhood education. Apart from learning, the curriculum also teaches resilience, empathy, and social competency. Developed from theories such as Vygotsky’s social development theory, as well as Goleman’s theory of emotional intelligence, SEL equips children to overcome social obstacles and thrive academically and outside the classroom. The study analyzes the transformational value of SEL and its advantages, from improved learning, more effective management of one’s feelings, to future mental well-being. The research also looks at evidence-based methods of integrating SEL throughout all early childhood curricula, such as contextualizing SEL within learning domains, teaching healthy school climate, and family and larger community involvement. The study also looks at challenges such as limited financing, teacher capacity, and cultural sensitivity and suggests how these challenges may be addressed. Drawing from effective SEL programs such as PATHS, Incredible Years, and Second Step, the study calls for systematic implementation to bring up emotionally intelligent, socially responsible children. The recommendations affirm SEL as an integral element of early childhood teaching that facilitates comprehensive children’s development and societal well-being.